Bio-orthopaedics : A New Approach - Gobbi, Alberto; Espregueira-Mendes, João; Lane, John G.; Karahan, Mustafa (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book introduces the exciting field of orthobiology, which will usher in a new array of therapeutic approaches that stimulate the body's natural resources to regenerate musculoskeletal tissues damaged by trauma or disease. The book addresses a range of key topics and discusses emerging approaches that promise to offer effective alternatives to traditional treatments for injuries to bone, cartilage, muscles, ligaments, and tendons. It explains in detail how a variety of innovative products, including biomaterials, growth factors, and autogenous cells, together provide the basis for the regeneration of these musculoskeletal structures and how recent scientific progress has created unique opportunities to address pathological situations that until recently have been treated with unsatisfactory results. The authors are experts from across the world who come together to provide a truly global overview. The book is published in collaboration with ISAKOS. It will be invaluable for all with an interest in this area of medicine, which has already attained huge popularity in Orthopaedics and Sports Medicine and has also attracted the attention of the lay public.
Keywords: Medicine.; Orthopedics.; Sports medicine.; elektronické knihy; electronic books